The influence of a weight-bearing platform on the mechanical behavior of two Ilizarov ring fixators: tensioned wires vs. half-pins - Gessmann, Jan (BioMed Central, 2011)
BACKGROUND: A weight-bearing platform applied at the distal end of an Ilizarov external frame allows patients with hindfoot transfixations, foot deformities or plantar skin lesions to bear weight. This leads to an indirect loading of the fracture or osteotomy site. However, the effect on the fracture/osteotomy site's motion or compressive loads is unknown. The aim of this study was to analyze the mechanical effects of a weight-bearing platform on the traditional all-wire, four-ring frame in comparison to a two-ring frame consisting of half-pins. METHODS: Two frame configurations, with either anatomically positioned wires or half-pins, were analyzed with and without a weight-bearing platform applied underneath the distal ring. Composite tibiae with a mid-diaphyseal osteotomy of 3.5 mm were used in all the experiments. An axial load was applied with the use of a universal test machine (UTS(®)). Interfragmentary movements, the relative movements of bone fragments and movements between rings were recorded using displacement transducers. Compressive loads at the osteotomy site were recorded with loading cells. RESULTS: Indirect loading with a weight-bearing platform altered the force transmission through the osteotomy. Indirect loading of the tibiae decreased the extent of the axial micro-motion by 50% under the applied weight load when compared to direct weight loading (p < 0.05). The half pin frame was 25% stiffer than the wire frame under both direct and indirect loading of the tibiae (p < 0.05). Compressive loads under indirect loading were reduced by 67% in the wire frame and by 57% in the half-pin frames compared to direct loading of the bones (p < 0.05). While axial loading in the wire frames resulted in plain axial movements at the site of the osteotomy, it was coupled with translational movements and angular displacements in the half pin mountings. This effect was more apparent in the case of indirect loading. CONCLUSIONS: A weight-bearing platform has substantial influence on the biomechanical performance of an Ilizarov external fixator. Half-pins induce greater stiffness to the Ilizarov external fixator and allow the usage of only one ring per bone segment, but shear stresses at the osteotomy under axial loading should be considered. The results allow an estimation of the size and direction of interfragmentary movements based on the extent of weight bearing.